Peran Kurasi Dalam Meningkatkan Kualitas Sumber Daya Informasi - Muhammad Luthfy Ihsan; Zulaikha, Sri Rohyati; Afrina, Cut (Media Informasi, 2025)
This study explores the critical role of curation in library collection development to ensure the availability of relevant and high-quality information resources. Curation is understood as a multifaceted process encompassing the selection, organization, and preservation of library materials to meet user needs in the digital age. Employing a literature review methodology, data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the Digital Curation Unit (DCU) model can be effectively applied in the context of library collection development. This model comprises several key stages: appraisal, ingest (digitization), classification, publication, and preservation. The implementation of DCU enhances collection quality and optimizes user experience. Effective curation not only addresses users’ evolving information needs but also ensures the continued relevance of collections in response to technological advancements. Furthermore, it supports the long-term preservation of information, securing sustainable access to knowledge resources. In conclusion, curation-based collection development plays a pivotal role in improving library services while supporting education and research. Through proper collection management, libraries can function as adaptive and reliable centers of knowledge.